ANALYSIS OF MATHEMATICAL REPRESENTATION OF PRE-SERVICE ELEMENTARY SCHOOL TEACHERS IN PROBLEM SOLVING BASED ON THINKING AND FEELING PERSONALITY TYPES - Alex Haris Fauzi; Robisha Zarifa Ribaah (International Conference on Humanity Education and Society (ICHES), 2025)
In the context of 21st-century mathematics education, the ability to construct andutilise mathematical representations is fundamental to successful problem solving,particularly for future elementary school teachers. However, the role of individualpersonality traits—especially the dichotomy between Thinking and Feeling types, asdefined by the Myers-Briggs Type Indicator (MBTI)—remains underexplored as afactor influencing representational strategies. This study addresses a critical researchgap by examining how these personality types affect the process of mathematicalproblem-solving. Using a qualitative descriptive approach with an intrinsic case studydesign, the research involved two prospective primary school teachers with distinctMBTI profiles. Data were collected through MBTI questionnaires, problem-solvingtasks, and task-based interviews, then analysed using thematic coding aligned withPolya’s problem-solving steps. The findings reveal distinct differences in the types andstructures of representations used: Thinking-type participants favoured symbolic andlogical representations. In contrast, Feeling-type participants relied more on intuitiveand narrative forms. These results highlight the impact of personality on cognitiveprocesses in mathematical reasoning. This paper contributes new insights to theintersection of mathematics education and personality psychology, with implicationsfor differentiated instruction in teacher education programs.